A Review on Coupled Inductor-Based High Step-Up DC-DC Converters for Renewable Energy Sources - Taha, Harwan M.; Ameen, Yasir M.Y.; Sadiq, Emad Hussen; Faqishafyee, Nizar Jabar (AI Society & STMIK Indonesia, 2024)
Renewable energy sources are increasingly being embraced due to their environmental advantages, characterized by clean energy production, including solar energy, fuel cells, and wind turbines. High step-up DC-DC converters are commonly employed in conjunction with these sources to elevate their unregulated output voltage to a high and regulated level. This is especially true for converters based on coupled inductors, which are able to achieve high voltage with a low duty cycle. This paper provides a comprehensive review on the coupled inductor-based high step-up DC-DC converters. This review involves five widely used topologies, namely stacked converters, cascaded converters, multi-winding converters, interleaved converters, and integrated converters. It is evident that the researchers proposing these converters aim to enhance the overall efficiency of the renewable energy system by achieving a high voltage gain with a low duty cycle, thereby reducing conduction losses, mitigating stress on switches, alleviating voltage spikes across the main switches, and recycling the leakage energy. However, it is noteworthy that some of the proposed circuit designs are complex and involve a high number of components resulting in increase in cost and size of packaging. Additionally, some proposed circuits could not effectively achieve the aforementioned objectives. This paper serves as a valuable resource for researchers, offering an overview of the latest developments in the high step-up converters based on coupled inductor, which may help them to identify potential research gaps.